A sexually dimorphic murine model of IUGR induced by embryo transfer. Issue 2 (February 2021) - Kaur, Harleen; Care, Alison S; Wilson, Rebecca L; Piltz, Sandra G; Thomas, Paul Q; Muhlhausler, Beverly S; Roberts, Claire T; Gatford, Kathryn L
Abstract : Animal models are needed to develop interventions to prevent or treat intrauterine growth restriction (IUGR). Foetal growth rates and effects of in utero exposures differ between sexes, but little is known about sex-specific effects of increasing litter size. We established a murine IUGR model using pregnancies generated by multiple embryo transfers, and evaluated sex-specific responses to increasing litter size. CBAF1 embryos were collected at gestation day 0.5 (GD0.5) and 6, 8, 10 or 12 embryos were transferred into each uterine horn of pseudopregnant female CD1 mice ( n = 32). Foetal and placental outcomes were measured at GD18.5. In the main experiment, foetuses were genotyped ( Sry ) for analysis of sex-specific outcomes. The number of implantation sites ( P = 0.033) and litter size (number of foetuses, P = 0.008) correlated positively with the number of embryos transferred, while placental weight correlated negatively with litter size (both P < 0.01). The relationship between viable litter size and foetal weight differed between sexes (interaction P = 0.002), such that foetal weights of males ( P = 0.002), but not females ( P = 0.233), correlated negatively with litter size. Placental weight decreased with increasing litter size ( P < 0.001) and was lower in females than males ( P = 0.020). Our results suggest that male foetuses grow as fast as permitted by nutrient supply, whereas the female maintains placental reserve capacity. This strategy reflecting sex-specific gene expression is likely to place the male foetus at greater risk of death in the event of a 'second hit'.